Identification, genotyping, and genomic comparison of Streptococcus porcinus isolated from diseased swine in Brazil - Matajira, Carlos E.C.; Moreno, Luisa Z. [UNESP]; Poor, Andre P.; Monteiro, Matheus S.; Gomes, Vasco T.D.M.; Dutra, Maurício C.; Barbosa, Mikaela R.F.; Sato, Maria I.Z.; Moreno, Andrea M. (Journal of Infection in Developing Countries, 2024)
Introduction: Streptococcus porcinus is considered a zoonotic opportunistic pathogen for several animal species, including swine, and can cause systemic clinical conditions. There are morphological similarities between streptococcal species, leading to possible incorrect diagnosis and inappropriate treatment choice. Here, we describe the identification, and genotypic and genomic characterization of S. porcinus isolated from 5 adult sick pigs from Minas Gerais and São Paulo (Brazil) between 2010–2017. Methodology: Streptococcus spp. strains were isolated from vaginal discharge, joint abscess, and brain tissue received for routine diagnosis. They were identified as S. porcinus by mass spectrometry and partial sequencing of the groEL gene. Genotypic characterization by amplified fragment length polymorphism was performed. In addition, the genome of one of the S. porcinus invasive strains was sequenced and comparative analyses were performed. Results: Genotyping revealed that the nervous system and joint abscess invasive strains had higher genetic similarity and clustered separately from vaginal discharge strains. Genome sequencing of one of the invasive strains revealed the presence of genes conferring resistance to erythromycin, tetracycline, lincosamides, and macrolides. A high level of similarity of the Brazilian strain genome with British and American strains was found. However, these strains also presented higher variation in their accessory genomes. Conclusions: The circulation of S. porcinus invasive and resistant strains, and the lack of its identification demands attention, posing a risk for animals and workers in the swine industry.
Keywords: genotyping; MALDI-TOF MS; resistance; Streptococcus porcinus; swine